Thoshihiko Izutsu’s Descriptive Significance in the Story of Maria in The Qur’an and His Approuch Techniques | Al-dala>lah Al-Was}fiyah li Tusyihi@ku> i>zutsu> ‘an Qis}s}oti Maryam Fi> Al-Qura>n Wa Taqniyatu Madkholiha>: الدلالة الوصفية لتوشيهيكو إيزوتسو عن قصة مريم في القرآن و تقنية مدخلها - Dian Risky Amalia; Asna Istianah; M Agus Mushodiq; Bety Dwi Pratiwi (Mantiqu Tayr: Journal of Arabic Language, 2022)
In Toshihiko Izutsu's book entitled Ethico-Religious Concept in the Qur'an, he states that his semantic study contains three parts. explain the methodological principles of semantic analysis, the positive and negative relationship of pre-Islamic tribal moral rules with Islamic Qur'anic ethics and the consistent application of the methodological rules that have been described. Basically, this thesis concludes that the study of the meaning of the Qur'an must be examined critically because the Qur'an presents its contents globally, so a critical study is needed to understand the message it contains. This research is a type of qualitative literature. The method used is to search for all Maryam words in the Qur'an and then group them after being divided into several groups, This research is qualitative literature. The method used is to search for all Maryam words in the Qur'an and then group them after being divided into several groups. The results of this study indicate that Toshihiko Izutsu's semantic approach is more effective than relying on translated text. This study also tries to apply this approach to Arabic learning, especially in meanings such as translation skills and Reading Comprehension. This approach seems suitable to be applied in order to minimize errors experienced by students in interpreting reading texts. Keywords: Story of Maryam, Semantics of Toshihiko Izutsu, influence and application.